Students' preferences towards language learning activities / Rohaida Jelani - Jelani, Rohaida (2013)
The purpose of the study is to determine and to investigate students' preferences towards language learning strategies and activities among Year 3 students in SK Bukit Naga, Klang. A set of questionnaire is used to obtains data from 40 students. The main objectives of the study are to determine which language learning activities are mostly preferred by students and to investigate what factors that influence students' preferences towards certain language learning activities. The findings show that the students are able to choose their own preferences towards language learning activities suggested. The language learning activity that mostly preferred by the students is art work. The three activities that mostly preferred by students are singing, doing art work and playing language game. The findings also revealed that the least preferred activity is learning grammar. Factors that influence students' preferences towards language learning activities are when teacher do the group activity and role play activities. Hopefully this study can help KSSR English Language teachers to choose suitable and interesting activities and strategies that can promote students' participations in teaching and learning session.